Studies on idiocerine leafhoppers with descriptions of Chinaocerus gen. nov. and three new species from China (Hemiptera: Cicadomorpha: Cicadellidae) - Dang, Li-Hong; Zhang, Bin; Li, Zi-Zhong (Zootaxa, 2016)
A new leafhopper genus of the tribe Idiocerini (Hemiptera: Cicadomorpha: Cicadellidae), Chinaocerus, is described from the southwest China together with three new species, C. kangdingensis Zhang & Li sp. nov. (Sichuan Province), C. bispinatus Zhang & Li sp. nov. (Yunnan Province) and C. shii Zhang & Li sp. nov. (Sichuan Province). Descriptions and illustrations of these three new species are provided, and a key for their separation is also given.